Inhibition of the SET8 Pathway Ameliorates Lung Fibrosis Even Through Fibroblast Dedifferentiation - Ugai, Keita; Matsuda, Shuichi; Mikami, Hideki; Shimada, Ayako; Misawa, Tomoko; Nakamura, Hiroyuki; Tatsumi, Koichiro; Hatano, Masahiko; Murayama, Toshihiko; Kasuya, Yoshitoshi (Frontiers in Molecular Biosciences, 2020)
Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease of unknown etiopathogenesis. The activation of extracellular matrix (ECM)-producing myofibroblasts plays a key role in fibrotic tissue remodeling. The dedifferentiation of myofibroblasts has attracted considerable attention as a promising target for the development of effective therapeutic interventions against IPF. Here, we screened a small library of epigenetics-related inhibitors using dedifferentiation assay of lung myofibroblasts prepared from a patient at the terminal stages of IPF and chose UNC0379. The inhibition of SET8, a histone H4 lysine 20 (H4K20) monomethyltransferase, by UNC0379 markedly suppressed the expression of α-smooth muscle actin (SMA) and ED-A-fibronectin in myofibroblasts. In IPF myofibroblasts, SET8 expression and H4K20 monomethylation (H4K20me1) levels, which were significantly higher than those in normal human lung fibroblasts, were reduced upon treatment with UNC0379. Hence, the changes in the expression of the two fibrotic markers clearly correlated with those in SET8 expression and H4K20me1 level. Furthermore, in a mouse model of bleomycin (BLM)-induced lung fibrosis, the intratracheal administration of UNC0379 at an early fibrotic stage markedly ameliorated the histopathological changes associated with collagen deposition in the lungs. However, treatment with UNC0379 did not significantly affect the number of proinflammatory cells or cytokine production in the bronchoalveolar lavage fluids from mice treated with BLM. In the BLM-injured lung, SET8 was predominantly localized to the nuclei of α-SMA-positive cells, which colocalized with H4K20me1. Taken together, our results indicate that the inhibition of SET8 resulting in myofibroblast dedifferentiation may partly mitigate lung fibrosis without affecting the inflammatory responses.